KEBIJAKAN PROTEKSI TENAGA KERJA INDONESIA DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN - Sintaningrum Sintaningrum; Liiklai Felfina (Universitas Muhammadiyah Jakarta, 2017)
ASEAN Economic Community (AEC) has just started in 2015, which means liberalism of goods and services within the 10 ASEAN countries has begun. The purpose of AEC in general is to increase competitiveness of ASEAN in attracting foreign investment and particularly to compete with China and India in world trade. ASEAN needs foreign investment to increase employment and its people welfares. Characteristic image of AEC is one single market and production base; economic region with high competitiveness; fair economic development region; and the region that integrates with global economic. There are positive and negative impacts of AEC for Indonesia especially for Indonesian workforce (labour). This study aims to analyse Indonesian Government policy in protecting Indonesia labour in facing the AEC that has just started in late 2015. This study was conducted using qualitative approach. Data collection of secondary data documents, news, literatures and report. Data are analysed using content analysis methods. The result shows that Indonesian government has prepared strategic planning and regulations in preparation of AEC era for the protection of Indonesian labour in facing liberalism of workforce within the ASEAN countries. But there are still need for improvement in term of: 1) evaluate and revise current law and regulations, and harmonise international instruments on labour protection; 2) Improve mo- nitoring; 3) Dissemination, training and advocacy to economic actor and stakeholders regarding AEC and labour protection; 4) further study on the issue is still needed.Keywords: Indonesian Labour, ASEAN Economic Community, Protection